ُEvaluation of efficiency of adjusted clear aligners by miniimplants in retraction of upper anterior teeth bulk: a randomized controlled trial - سعيد غزوان; حسن حازم (Latakia University Journal -Medical Sciences Series, 2023)
Retraction of anterior teeth bulk in clear aligners are quite difficult specifically when bodily movement need to be achieved . adding mini screws with splitting the aligner can improve the efficiency of clear aligners. Aim of the study : comparing the efficiency of adjusted clear aligners with the conventional brackets in retracting teeth bulk after extraction of premolars. Materials and method: A 12 patients aged between (18-25) years treated with first upper premolar extraction and retraction of the anterior teeth bulk with adjusted clear aligners in a study group and conventional brackets in control group using miniscrews in both groups. Result : both groups were able to achieve the aimed result with a great advance in esthetic side for the study group.